Effect of Kinesthetic Learning on Students’ Interest and Achievement in Mathematics - Abah, Joshua; Chinaka, Taurayi Willard; Ogbiji, Emmanuel Ogar (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
One of the pertinent reasons for poor academic achievement in Mathematics is fundamentally linked to the application of ineffective teaching methods by teachers to impact knowledge to learners. This study adopts a quasi-experimental pre-test post-test research design to examine the efficacy of kinesthetic learning on interest and achievement in Mathematics. Four research questions were raised to guide the study and four hypotheses were formulated and tested at 0.05 level of significance. The sample comprises 101 Junior Secondary School students drawn from two secondary schools in Bekwarra Local Government Area of Cross River State, Nigeria. Two intact classes were randomly selected from each school and assigned to experimental and control group. Data for the study were sourced using a modified Mathematics Interest Inventory (MII) and mathematics achievement test designed by the researchers tagged Students’ Mathematics Achievement Test (SMAT). Data collected were analyzed using mean, standard deviation and Analysis of Covariance (ANCOVA). The findings revealed a high post-test interest cluster mean of 3.10 (above the decision benchmark of 2.50) and also a higher post-test mean achievement score with (Mean = 20.82; Standard Deviation = 3.63) for students in the experimental group compared to the control group. The result also indicated that both male and female students taught mathematics using kinesthetic learning in the experimental group had positive interest and achievement after exposure to the treatment. The test of the hypotheses indicated that there is significant difference in interest and achievement between students taught mathematics using kinesthetic learning and conventional method, whereas there is no significant difference on the interest and achievement of male and female students taught mathematics using kinesthetic learning. The study concluded that kinesthetic learning has a positive effect on interest and achievement in mathematics; and that gender is not a sole determinant of good academic performance or interest in mathematics but teaching method. The study recommended that mathematics teachers should adopt kinesthetic learning or play way method in teaching because of its relevance in improving learners’ interest and achievement.